Analysis of Complaints to a Tertiary Care Pain Clinic Over a Nine-Year Period - Angela Mailis-Gagnon; Keith Nicholson; Luis Chaparro (Pain Research and Management)
BACKGROUND: The present study is the result of an internal audit and examines the profiles of complainants and the sources and nature of complaints toward the staff in a tertiary care pain clinic, the Comprehensive Pain Program of the Toronto Western Hospital in Toronto, Ontario.